Penguatan pendidikan antikorupsi melalui integrasi kurikulum dan budaya Sekolah - Nuryatin, Yunita (Maliki Interdisciplinary Journal, 2026)
Anti-corruption education is important to implement from an early age because corruption is not only related to legal violations but also indicates weak character, integrity, and social responsibility. This study used a descriptive qualitative method with a library research approach. Data were obtained through a review of journals, scientific articles, books, and documents relevant to anti-corruption education, character education, curriculum, and school culture. The results of the discussion indicate that the integration of anti-corruption education can be achieved through learning objectives, materials, methods, teaching tools, and assessments. Furthermore, school culture serves as a practical space for anti corruption values through role models, fair rules, a prohibition on cheating, transparency of class funds, an honest canteen, and student council activities. A model for strengthening anti-corruption education needs to be built through an integration of the curriculum, school culture, role models, and participation of the school community. Thus, anti-corruption education does not remain a theory but becomes a real habit in school life.